Quality of life among female cancer survivors in Africa: An integrative literature review - Rhoda Suubi Muliira; Anna Santos Salas; Beverley O'Brien (Elsevier, 2017)
Quality of life (QOL) has been studied extensively among cancer populations in high income countries where cancer care resources are available to many. Little is known concerning the QOL of cancer groups residing in Africa where resources can be scarce. The integrative review of the literature explored and critically examined studies that had addressed QOL in female cancer survivors in Africa. The extent to which QOL studies incorporated a cultural perspective was also examined. Research studies published between 2005 and 2015 were retrieved from five databases: CINAHL, MEDLINE, SCOPUS, ProQuest dissertations and Theses full text, and GlobalHealth. Primary qualitative or quantitative studies regardless of sample size or setting were included. A total of 300 studies were identified and 28 full text studies were retrieved and assessed for eligibility. Eight studies met inclusion criteria. Factors that affected the QOL were socio-demographic especially age, education, employment, income and residence; illness-related factors such as having advanced cancer and multiple symptoms; treatment-related factors associated with surgery and radiotherapy; psychosocial factors such as support and anxiety; and cultural factors including fatalism and bewitching. Practice implications entail increasing awareness among nurses and allied healthcare providers of the potential effects on QOL of a cancer diagnosis and treatment of female cancers such as pain, fatigue, sexual dysfunction, hormonal and body image changes, anxiety, depression and cultural practices. Failure to identify and deal with these may result in poor treatment adherence, low self-esteem, and ultimately poor QOL.